The valuation of amounts for the purpose of inclusion in gross income - Spearman, Tarryn Leigh (Rhodes University, Faculty of Commerce, Department of Accounting, 2012)
The present research investigates the valuation of amounts for the purpose of inclusion in gross income. Because the gross income definition in section 1 of the Income Tax Act includes "amounts in cash or otherwise", valuations are often required in order to establish a value in money terms for amounts received or accrued in a form otherwise than in cash. The basis on which these valuations are made can vary and the courts have frequently been called upon to decide on the correct method of valuation. There has been an ongoing debate in the courts as to whether a strict objective approach or a more flexible subjective approach should be adopted when valuing an amount in a form other than cash, which was finally settled in the decision by the Supreme Court of Appeal in CIR v Brummeria Renaissance (Pty) Ltd, which held that an objective approach must be followed. The present research will demonstrate how the strict rule of interpretation tends to result in purely objective valuations as it requires that the ordinary grammatical meaning of words be applied and does not allow the court to consider the purpose of the legislation or introduce any subjectivity based on the circumstances of each individual taxpayer and the facts of each particular case, which a purposive interpretation approach does. The purposive approach to interpretation is therefore more closely aligned with the subjective approach to valuation. Both the objective and subjective approaches to valuation have advantages and disadvantages, which are addressed in the research. The need for certainty in taxation was articulated as early as 1776 by Adam Smith in his Wealth of Nations. The objective approach appears to create a level of consistency as all income received by a taxpayer is effectively taxed as if received by a third party in an arm's length transaction. The approach has led to unfair decisions at odds with economic reality and generally accepted accounting principles, which could be challenged on the basis of a lack of equity and fairness as required by the Constitution of the Republic of South Africa. The research demonstrates that an objective method of valuation is neither fully objective nor appropriate in certain circumstances, while a subjective approach may be more appropriate as it ensures that each taxpayer's individual rights are protected. Although the subjective approach successfully addresses the issue of fairness, it threatens to introduce an unacceptable level of inconsistency and is, in reality, not always administratively feasible. The present research concludes that a trade-off between fairness and consistency is often necessary.
Keywords: Uncatalogued